The problem of screening in the aspect of comparative literature - Nurmanova Ж.К.; Zhapanova М.Е. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
In this article, the art of film adaptation is considered in the aspect of comparative literary criticism as the area of intersection of literary and screen texts. The authors of the article turn to the history of the issue, focus on the ambiguities of both the interpretation of the term and approaches to film adaptations. Particular attention is paid to the types of adaptations: canonical, free, modernized, etc. The article analyzes in detail the issues of transformation of the genre, plot and images that are inevitable when transcribing a literary text into the language of cinema